Sosialisasi Optimalisasi Sampah Dari Drum Plastik Bekas Guna Menjaga Kebersihan Lingkungan - Wildan Febriadi; Nafiudin Nafiudin; Ratu Erlina Gentari (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Environmental health problems are one of the social problems in life that have not been resolved since then until now. Individuals' lack of awareness of cleanliness is a factor that greatly influences environmental health. Therefore, providing understanding to the public regarding the importance of maintaining environmental cleanliness, especially in managing household waste, must be improved. Raising public awareness to live clean and free from waste is our common goal, not only for people in urban areas but also for people in rural areas. The lack of knowledge and awareness of the people of Serang Subdistrict regarding the importance of protecting the environment, and how to manage waste, can be seen from the large number of Serang Subdistrict residents who throw rubbish in gardens and even rivers, as well as the lack of rubbish bins in homes or in public places. To raise public awareness about caring for the environment requires education that must be carried out continuously, in order to change people's habits and mindset. This service aims to raise public awareness about throwing away rubbish in its proper place and socializing how to make rubbish bins from used plastic drums. The author uses the PAR (Participatory Action Research) method to solve environmental problems. The activities take the form of socializing information about environmental cleanliness and providing training to the community to make trash cans from items around us that are no longer used, one of which is using used plastic drums. The result of the activity is an increase in public knowledge of the importance of maintaining environmental cleanliness through the use of trash cans that have been made in view of the residential environment being free of rubbish, as well as the community's ability to make their own trash cans from used plastic drums.